2013
DOI: 10.1371/journal.pone.0063204
|View full text |Cite
|
Sign up to set email alerts
|

Age-Specific Gene Expression Signatures for Breast Tumors and Cross-Species Conserved Potential Cancer Progression Markers in Young Women

Abstract: Breast cancer in young women is more aggressive with a poorer prognosis and overall survival compared to older women diagnosed with the disease. Despite recent research, the underlying biology and molecular alterations that drive the aggressive nature of breast tumors associated with breast cancer in young women have yet to be elucidated. In this study, we performed transcriptomic profile and network analyses of breast tumors arising in Middle Eastern women to identify age-specific gene signatures. Moreover, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(117 citation statements)
references
References 92 publications
(183 reference statements)
2
115
0
Order By: Relevance
“…TPX2 is a cell cycle protein and serves a key role in the stability of the mitotic spindle (18). As a microtubule-associated protein, TPX2 tightly adheres to the mitotic spindle in mitotic cells (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TPX2 is a cell cycle protein and serves a key role in the stability of the mitotic spindle (18). As a microtubule-associated protein, TPX2 tightly adheres to the mitotic spindle in mitotic cells (28).…”
Section: Discussionmentioning
confidence: 99%
“…TPX2 expression is closely regulated by the cell cycle, and exhibits particularly high expression in proliferating cells transitioning between the G 1 and S phase (12)(13)(14). Certain studies have demonstrated that the TPX2 gene, in addition to elevated gene copy numbers, is frequently identified in various human malignancies, including lung carcinoma (15), salivary gland cancer (16), esophageal cell carcinoma (17) and breast cancer (18). Furthermore, the upregulated expression of TPX2 has been observed in a number of different tumors, including bladder and colon cancer (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…Colak et al 31 analyzed the expression signatures of breast tumors in Middle-Eastern YWBC using genomewide gene expression assays. They compared the transcriptome from BC tumors in three different age cohorts from young women (< 45 years), pre-elderly women (45-55 years) and elderly patients (> 55 years).…”
Section: Tumor Gene Expression Profilingmentioning
confidence: 99%
“…Starting from the well documented assumption that the tumor growth is dependent on the development of the vasculature, showing the correlation between the age of patients and the vessel density in tumors that were diagnosed can, in some way, correspond to the differences observed in some cancers concerning the dynamics of tumor growth depending on the age of a patient. Such kind of studies were conducted in breast or thyroid cancer [10][11][12].…”
Section: Discussionmentioning
confidence: 99%